4CPS-262 Evaluation of a pharmacist-led discharge service. (2nd March 2018) - Ryan, F; McCool, S; Byrne, S
Abstract : Background: Medication errors can occur at any transition of patient care. However, evidence suggests that medication errors are more common on discharge. Medication reconciliation at transitions in a patient's care have been found to reduce the risk to patient safety and improve communication between care settings. Purpose: The aim of this study was to determine if the discharge prescription for patients receiving a pharmacist-led discharge service had a greater compliance with the Health Information and Quality Authority (HIQA) National Standard for Patient Discharge Summary Information than patients receiving standard pharmacy services and no pharmacy services. The study also aimed to determine the acceptability of the service to all stakeholders and to assess the effectiveness and user acceptability of an electronic medication reconciliation system versus a paper-based system. Material and methods: Discharge prescriptions were audited against the HIQA National Standard for Patient Discharge Summary Information. The intervention group consisted of 94 patients who received a pharmacist medication reconciliation on admission and discharge, along with preparation of the discharge prescription and communication of the discharge prescription to the GP and community pharmacy. The two control groups consisted of one group of 100 patients who had a pharmacist medication reconciliation on admission, and the other group of 100 patients who received no pharmacy services. Satisfaction surveys were circulated to all stakeholders. Results: This study found that pharmacist involvement in the preparation of a patient's discharge prescription improved compliance with the HIQA National Standard for Patient Discharge Summary Information. Pharmacist involvement reduced the ambiguity associated with incomplete medication information. Improved quality of the discharge prescription was determined in the satisfaction surveys undertaken by GPs, community pharmacists and hospital doctors. The key benefits of the service according to the stakeholders were time saving, increased patient safety, fewer queries and clearer prescriptions with more information. eClinical discharge prescriptions had a higher compliance with the HIQA National Standard for Discharge Summary Information. Conclusion: This study has proven that pharmacist involvement in the preparation of a patient's discharge prescription improves compliance with the HIQA National Standard for Patient Discharge Summary Information. References and/or Acknowledgements: HIQA National Standard for Patient Discharge Summary Information 2013. No conflict of interest